Tendência secular de mortalidade por doenças infecciosas no estado de Sergipe - Albuquerque, Marcos Antonio Costa de (2016)
The present study analyzed trends in communicable disease mortality in the State of Sergipe, Brazil over a period of 34 years. The purposes were to determine secular trends in mortality from these diseases, to identify age groups of greater mortality rates, and for SIDA, to determine incidence as well as mortality. It was an ecological study of time series and data were retrieved from the System of Information on Notifiable Diseases (SINAM) and System of Mortality Information (SIM) of the Health Agency of the State of Sergipe. The Joinpoint Regression Program of the National Cancer Institute, USA, performed trend analyses. The results we found showed that sepsis and gastroenteritis had greater mortality rates. The subset of Neglected Tropical Diseases (NTD) presented growing mortality trends, mainly schistosomiasis and Chagas’ disease; tuberculosis had growing trends only in males; and SIDA presented rising incidence and mortality trends in both genders, except in some age groups. It is imperative to implement new strategies in surveillance, treatment, and monitoring of specific diseases; to redesign SIDA control policies, particularly concerning to prevention, diagnosis, and care of the seropositive individuals.